Implementation of an Anti-Bullying Program in a Child-Friendly Elementary School: A Case Study at SD Negeri 2 Dempel - Moh Nurkhasan; Widya Kusumaningsih; Joko Sulianto (MASI Mandiri Edukasi, 2026)
Bullying in schools remains a serious problem that can negatively affect students’ psychological well-being, learning motivation, and social development. Therefore, effective school management is required to implement preventive programs that create a safe and supportive learning environment. This study aims to analyze the management of the anti-bullying program within the Child-Friendly School program at SD Negeri 2 Dempel, Karangrayung, Grobogan, focusing on four management functions: planning, organizing, actuating, and controlling. This research employs a qualitative, descriptive approach. The research subjects include the principal, teachers, the school committee, and the Child-Friendly School team. Data were collected through observation, interviews, and documentation. The data analysis process involved data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the program implementation. The results show that the anti-bullying program management at SD Negeri 2 Dempel has been implemented effectively. In the planning stage, the school conducts needs identification through observation, questionnaires, interviews, and analysis of student discipline data. The organizing stage involves establishing a clear organizational structure, allocating school resources, and assigning tasks based on staff competencies. In the actuating stage, the principal provides guidance and motivation to ensure program implementation through activities such as integrating anti-bullying values into learning, developing child-friendly habits, supervising vulnerable areas, providing counseling services, collaborating with parents, and conducting anti-bullying campaigns. In the controlling stage, supervision is carried out through routine evaluations, principal monitoring, and follow-up improvements. Overall, the program contributes to creating a safe, inclusive, and child-friendly school environment.